Dilated inferior vena cava: Common echocardiographic findings in top level elite athletes - Goldhammer, E.; Abinader, E. G.; Sagiv, M. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Typical structural features of the athlete`s heart as defined by echocardiography has been extensively described, however information concerning extracardiac structures as the inferior vena cava is scarce. 58 top level athletes and 30 healthy matched controls (age range 18-27) underwent a complete Doppler-echo study. Inferior vena cava (IVC) diameter was determined in the subxyphoid approach, 10-20 mm away from its junction to the right atrium. Measures reflect the median values between maximal inspiratory and expiratory values. IVC respiratory collapsibility index was determined as well.